The leadership fo schools in three regions in Portugal based on the findings of external evaluation - Quintas, Helena (2014)
School leadership has significant effects on the learning, development and academic success of the pupils and on the quality of educational organisations, so, to a large extent, the effectiveness of the school depends upon the way in which leadership is carried out. It is on this basis that we undertook our study which led in this article. In it we sought to characterise the leadership of schools and school clusters in the regions of the Algarve, Alentejo and Lisbon and Tagus Valley, globally and specifically, based on the analysis of the content of external evaluation reports produced by teams from the General Inspectorate of Education during the 2006/2007, 2007/2008 and 2008/2009 academic years. This analysis was carried out as part of the research project FSE/CED/83489/2008 under the responsibility of the Centre for Sociology Research and Studies from the Lisbon University Institute, the University of the Algarve and the Barafunda Association, and we were part of the respective research team. By analysing the data we have been able to establish a joint and per region “profile” of the leaderships in the schools and school clusters that were evaluated, although we onsider that their results cannot be extrapolated, given he imits in the wording of the valuation reports and the fact at these reports were produced by different teams from egion to region and even within the regions themselves.